Extending abstract argumentation systems theory. - Baroni, P. (Artificial intelligence.)
n this paper, we extend the previous termtheory of abstract argumentation systemsnext term proposed by Vreeswijk (1997). This framework stands at a high abstraction level and provides a general model for previous termargumentationnext term activity. However, the previous termtheorynext term reveals an inherent limitation in that the premises of the previous termargumentationnext term process are assumed to be indefeasible, and this introduces the need of an implicit constraint on the strength of the arguments, in order to preserve correctness. In many application contexts the information available to start reasoning is not guaranteed to be completely reliable, therefore it is natural to assume that premises can be discarded during the previous termargumentationnext term process. We extend the previous termtheorynext term by admitting that premises can be defeated and relaxing the implicit assumption about their strength. Besides fixing the technical problems related to this hidden assumption (e.g., ensuring that warranted arguments are compatible), our proposal provides an integrated model for belief revision and defeasible reasoning, confirming the suitability of previous termargumentationnext term as a general model for the activity of intelligent reasoning in presence of various kinds of uncertainty.